Application of Problem-Based Learning Model Assisted by Quizziz Game Media to Improve Learning Outcomes in Exposition Text Material in Class X SMK 7 Semarang - Ngatmini; Sri Kismiyati; Amelia Putri, Almawati (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
Education in the digital era is experiencing rapid development with various informative and innovative technologies. One of them is the digital learning platform Quizizz, an interactive learning platform that can be integrated into the application of Problem Based Learning (PBL) models. The application of the Problem Based Learning (PBL) Model assisted by Quizziz media in Vocational High Schools (SMK) has the potential to improve student learning outcomes, in this study is the exposition text material of Indonesian subjects in Class X. However, comprehensive research on the effectiveness of the Problem Based Learning Model (PBL) assisted by Quizziz media in SMK is still limited. Therefore, this study aims to determine whether there is an improvement in student learning outcomes by applying the Problem Based Learning (PBL) Model assisted by Quizziz media. This research uses a quasi-experimental method with a quantitative approach. The research sample consisted of all Class X students of SMK 7 Semarang. The experimental class applies the Problem Based Learning (PBL) Model assisted by Quizziz media, while the control class does not use Queziz media. The results showed improved student learning outcomes in both groups. However, the most significant improvement in learning outcomes occurred in the group that used the educational game application Quizizz. This study supports the hypothesis that the use of Quizizz can improve student learning outcomes in the exposition text material of Grade 7 Indonesian subjects. These results make an important contribution to our understanding of the application of the Quizziz media-assisted Problem Based Learning (PBL) Model as a learning tool in vocational schools and its implications for student learning outcomes Keyword: Learning Outcomes; Problem Based Learning; Quizizz